Dynamic Resource Sharing in 5G with LSA: Criteria-Based Management Framework - Sadreddini, Zhaleh; Mašek, Pavel; Cavdar, Tugrul; Hošek, Jiří; Gudkova, Irina; Andreev, Sergey (Hindawi, 2018)
Owing to a steadily increasing demand for efficient spectrum utilization as part of the fifth-generation (5G) cellular concept, it becomes crucial to revise the existing radio spectrum management techniques and provide more flexible solutions for the corresponding challenges. A new wave of spectrum policy reforms can thus be envisaged by producing a paradigm shift from static to dynamic orchestration of shared resources. The emerging Licensed Shared Access (LSA) regulatory framework enables flexible spectrum sharing between a limited number of users that access the same frequency bands, while guaranteeing better interference mitigation. In this work, an advanced user satisfaction-aware spectrum management strategy for dynamic LSA management in 5G networks is proposed to balance both the connected user satisfaction and the Mobile Network Operator (MNO) resource utilization. The approach is based on the MNO decision policy that combines both pricing and rejection rules in the implemented processes. Our study offers a classification built over several types of users, different corresponding attributes, and a number of operator's decision scenarios. Our investigations are built on Criteria Based Resource Management (CBRM) framework, which has been specifically designed to provide results for dynamic LSA management in 5G mobile networks. To verify the proposed model, the results (spectrum utilization, estimated secondary user price for the future connection, and user selection methodology in case of user rejection process) are validated numerically as we yield important conclusions on the applicability of our approach, which may offer valuable guidelines for efficient radio spectrum management in highly-dynamic and heterogeneous 5G environments.

Owing to a steadily increasing demand for efficient spectrum utilization as part of the fifth-generation (5G) cellular concept, it becomes crucial to revise the existing radio spectrum management techniques and provide more flexible solutions for the corresponding challenges. A new wave of spectrum policy reforms can thus be envisaged by producing a paradigm shift from static to dynamic orchestration of shared resources. The emerging Licensed Shared Access (LSA) regulatory framework enables flexible spectrum sharing between a limited number of users that access the same frequency bands, while guaranteeing better interference mitigation. In this work, an advanced user satisfaction-aware spectrum management strategy for dynamic LSA management in 5G networks is proposed to balance both the connected user satisfaction and the Mobile Network Operator (MNO) resource utilization. The approach is based on the MNO decision policy that combines both pricing and rejection rules in the implemented processes. Our study offers a classification built over several types of users, different corresponding attributes, and a number of operator's decision scenarios. Our investigations are built on Criteria Based Resource Management (CBRM) framework, which has been specifically designed to provide results for dynamic LSA management in 5G mobile networks. To verify the proposed model, the results (spectrum utilization, estimated secondary user price for the future connection, and user selection methodology in case of user rejection process) are validated numerically as we yield important conclusions on the applicability of our approach, which may offer valuable guidelines for efficient radio spectrum management in highly-dynamic and heterogeneous 5G environments.
Dynamic Resource Sharing in 5G with LSA: Criteria-Based Management Framework
Keywords: Licensed Shared Access; 5G; Spectrum management; Heterogeneous networks; Dynamic resource orchestration; Licensed Shared Access; 5G; Spectrum management; Heterogeneous networks; Dynamic resource orchestration